Exploring the state of economic well-being among urban Malay civil servants: a qualitative study - Mohamed Harith, Nor Hafizah; Md. Noon, Hazizan (Elsevier Ltd, 2015)
This research aims to explore how the economic well-being affects the subjective well-being (SWB) among the selected respondents who live in the major cities in the Klang Valley, Malaysia. Adopting the Allard's dimensions of welfare, this study explores the subjective meaning of life satisfaction among the administrative personnel of a Malaysian university, namely Universiti Teknologi MARA (UiTM). Sixteen key informants from four different categories of administrative staff of the University’s main campus in Shah Alam, Selangor were engaged in the researchers’ in-depth interviews. The main findings of this research have shown that the responses centred around the different coping abilities adopted by the urban Malay civil servants to survive life in the urban areas.